VALDAIAN GLACIAL MAXIMA IN THE ARKHANGELSK DISTRICT OF NORTHWESTERN RUSSIA - Demidov I.N.; Houmark-Nielsen M.; Kjr K.H.; Funder S.; Larsen E.; Lys A.; Lunkka J.-P.; Saarnisto M. (My University, 2004)
The marginal configurations and ages of the Valdaian (Weichselian) glacial maxima in northern Russia have hitherto not been well established, thus, numerous versions of the Last Glacial Maximum (LGM) positions of the Scandinavian Ice Sheet are known (Fig.1B). New data on ice sheet growth and decay indicate at least three glacial maxima during the Late Pleistocene each with individual spreading centres and different ages. Results of modern investigations in the Arkhangelsk region, conducted by the authors, are compared with an analysis of previous data on the Late Quaternary geology of Northwest Russia, which comprises a thorough presentation of Russian literature on this subject. This has allowed us to question and revise former models on Valdaian glaciation history and icemarginal positions in a major part of the Russian North.